Network Signaling Channel for Improving ZigBee Performance in Dynamic Cluster-Tree Networks - Kohvakka Mikko; Suhonen Jukka; Kuorilehto Mauri; Hännikäinen Marko; Hämäläinen D (EURASIP Journal on Wireless Communications and Networking, 2008)
Abstract ZigBee is one of the most potential standardized technologies for wireless sensor networks (WSNs). Yet, sufficient energy-efficiency for the lowest power WSNs is achieved only in rather static networks. This severely limits the applicability of ZigBee in outdoor and mobile applications, where operation environment is harsh and link failures are common. This paper proposes a network channel beaconing (NCB) algorithm for improving ZigBee performance in dynamic cluster-tree networks. NCB reduces the energy consumption of passive scans by dedicating one frequency channel for network beacon transmissions and by energy optimizing their transmission rate. According to an energy analysis, the power consumption of network maintenance operations reduces by 70%–76% in dynamic networks. In static networks, energy overhead is negligible. Moreover, the service time for data routing increases up to 37%. The performance of NCB is validated by ns-2 simulations. NCB can be implemented as an extension on MAC and NWK layers and it is fully compatible with ZigBee.